2014
DOI: 10.1017/s1092852914000480
|View full text |Cite
|
Sign up to set email alerts
|

The role of reproductive hormones in postpartum depression

Abstract: Despite decades of research aimed at identifying the causes of postpartum depression (PPD), PPD remains common, and the causes are poorly understood. Many have attributed the onset of PPD to the rapid perinatal change in reproductive hormones. Although a number of human and non-human animal studies support the role of reproductive hormones in PPD, several studies have failed to detect an association between hormone concentrations and PPD. The purpose of this review is to examine the hypothesis that fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
249
3
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(268 citation statements)
references
References 159 publications
(266 reference statements)
7
249
3
9
Order By: Relevance
“…This study also delineates the differences between PPD and antenatal depression continuing after childbirth. Further, a study has suggested "hormone sensitive postpartum depression" to be a subgroup who are sensitive to hormonal changes of childbirth (Schiller et al 2015).…”
Section: Etiology and Risk Factors:-mentioning
confidence: 99%
“…This study also delineates the differences between PPD and antenatal depression continuing after childbirth. Further, a study has suggested "hormone sensitive postpartum depression" to be a subgroup who are sensitive to hormonal changes of childbirth (Schiller et al 2015).…”
Section: Etiology and Risk Factors:-mentioning
confidence: 99%
“…Findings from several studies implicate peripartum fluctuations in reproductive hormones (particularly, the major progesterone metabolite allopregnanolone) having pivotal pathophysiological roles in PPD [3]. The rapid decline in the levels of reproductive hormones that occurs after delivery is believed to contribute to the development of depression in susceptible women.…”
Section: Editorialmentioning
confidence: 99%
“…Replication of these results in larger, independent cohorts is warranted. Understanding of the pathways by assessing biological markers such as longitudinal changes in gene expression and DNA methylation would be useful [15].…”
Section: Mean (Sd)/n (%)mentioning
confidence: 99%